2022
DOI: 10.1002/ame2.12218
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a preclinical dry eye model in New Zealand white rabbits during and following topical instillation of 1% ophthalmic atropine sulfate

Abstract: Background:The objective of this study was to validate an animal model for dry eye during and after the administration of 1% ophthalmic atropine sulfate (OAS) in New Zealand white (NZW) rabbits.Methods: OAS (1%) was applied three times per day to 30 eyes of 15 healthy NZW rabbits. Sacrifice, enucleation, and lacrimal gland removal took place on days 15, 21, and 30 (OAS group). A second group (n = 5) was used as control. Clinical evaluations took place on days 3, 10, 15, 18, 21, 24 and 30. The primary endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have reported that anticholinergic agents such as atropine could impede these neural reflex loops in a rabbit dry-eye model. 34 37 This study also revealed that 0.05% atropine had significant effects on NIKBUT-first, NIKBUT-average, and OSDI, with the latter exceeding the normal upper limit of 12. However, 0.01% atropine eyedrops had minimal impact on ocular surface characteristics.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have reported that anticholinergic agents such as atropine could impede these neural reflex loops in a rabbit dry-eye model. 34 37 This study also revealed that 0.05% atropine had significant effects on NIKBUT-first, NIKBUT-average, and OSDI, with the latter exceeding the normal upper limit of 12. However, 0.01% atropine eyedrops had minimal impact on ocular surface characteristics.…”
Section: Discussionmentioning
confidence: 52%